Interaction of tyrosine residues with the chromophore in bacteriorhodopsin. Issue 7 (July 1985) - Takeda, Kazuo; Iwasa, Tatsuo; Tokunaga, Fumio; Packer, Lester
Abstract : We previously reported that the absorption spectrum at low temperatures of iodinated bacteriorhodopsin can be separated into four components with maxima at shorter wavelengths than in native bacteriorhodopsin. In this study, the time course of the formation of each spectral component after iodination was analyzed, revealing that these four components correspond to four different iodinated states of tyrosine residues interacting with the retinal chromophore of bacteriorhodopsin. Therefore at least two tyrosine residues interact with the chromophore of bacteriorhodopsin.